ANALYSIS OF THE IMPLEMENTATION OF ACEH QANUN NUMBER 11 OF 2018 ON ISLAMIC BANKING IN THE CITY OF BANDA ACEH, INDONESIA - Aiman, Muhammad; Muhammad Syuib (JURISTA: Jurnal Hukum dan Keadilan, 2025)
The Qanun Aceh serves as a legal instrument mandating the conversion of all conventional financial institutions into Islamic-based financial entities, as part of the comprehensive implementation of sharia law in the financial sector. This study employs a qualitative-descriptive method, drawing on a juridical and Islamic economic approach, supported by field observations and interviews with banking customers and practitioners. The findings indicate that the implementation of the Qanun has been structurally well-executed, as reflected in the transformation of banking contracts (akad) and services in accordance with sharia principles. The effectiveness of the implementation is evident in the growing public trust and increased utilisation of Islamic financial products. However, efficiency remains a challenge, particularly in terms of financial literacy, human resource capacity, and comprehension of Sharia-compliant contracts. The socio-economic implications of the Qanun's implementation include the reinforcement of Islamic economic justice values, increased Islamic financial inclusion, and the potential empowerment of the Muslim community's economy. This research recommends strengthening Islamic financial literacy and enhancing collaboration among government authorities, banking institutions, and religious scholars to ensure the sustainable and holistic enforcement of the Qanun.